Stock Valuation Analysis of Dividend Discount Model, Free Cash Flow to Equity and Walter Model in Investment Decision - Apriliana Ika Kusumanisita; Frilya Hajar Minanti (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
This study aimed to (1) test the influence of stock valuation with dividend discount model (DDM) method on investment decisions, (2) test the influence of stock valuation with Free Cash Flow to Equity (FCFE) method on investment decisions, and (3) test the influence of stock valuation with Walter Model method on investment decisions in Consumer Good Industry Companies listed in ISSI period 2016-2019. 24 Companies in the Consumer Good Industry sector were sampled in this study. The data used was secondary data. The results of this study show that the Dividend Discount Model (DDM) has a significant positive influence on investment decisions, while the Free Cash Flow to Equity (FCFE) and Walter Model methods do not have a significant influence on investment decisions